Temperature induced conformational transitions of elastin-like polypentapeptides studied by Raman and NMR spectroscopy. Issue 3 (2002) - Dybal Dybal, Jiří Jiří; Schmidt Schmidt, Pavel Pavel; Kurková Kurková, Dana Dana; Kříž Kříž, Jaroslav Jaroslav; Rodríguez-Cabello Rodríguez-Cabello, José Carlos José Carlos; Alonso Alonso, Matilde Matilde
Abstract : Raman and NMR spectroscopy together with DFT quantum chemical calculations have been used to elucidate conformational changes occurring during inverse temperature transition in water solution of two elastin‒like polypentapeptides, poly(G1 V1 G2 V2 P) and poly(AV1 GV2 P). From the temperature dependences of Raman spectra and 1 H– 1 H NOESY spectra follows that above the transition temperature a β (II)‒turn conformational structure is formed on the residue located between Pro and Val1 .